2021
DOI: 10.3389/fmicb.2021.658292
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk Between Butyric Acid and Gut Microbiota in Ulcerative Colitis Following Fecal Microbiota Transplantation

Abstract: Fecal microbiota transplantation (FMT) can inhibit the progression of ulcerative colitis (UC). However, how FMT modulates the gut microbiota and which biomarker is valuable for evaluating the efficacy of FMT have not been clarified. This study aimed to determine the changes in the gut microbiota and their relationship with butyric acid following FMT for UC. Fecal microbiota (FM) was isolated from healthy individuals or mice and transplanted into 12 UC patients or colitis mice induced by dextran sulfate sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…Consistent with our previous studies [ 17 20 ], we found that DSS-triggered acute and chronic colitis were similar in terms of disease activity, colon shortening and histopathological changes in the colon, but differed remarkably in terms of gut microbiota profiles. Given that the initiation and progression of UC centers heavily on gut microbiota proportions, the therapeutic potential of fecal microbiota transplantation is increasingly being assessed in UC animal models.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our previous studies [ 17 20 ], we found that DSS-triggered acute and chronic colitis were similar in terms of disease activity, colon shortening and histopathological changes in the colon, but differed remarkably in terms of gut microbiota profiles. Given that the initiation and progression of UC centers heavily on gut microbiota proportions, the therapeutic potential of fecal microbiota transplantation is increasingly being assessed in UC animal models.…”
Section: Introductionsupporting
confidence: 92%
“…DSS and 2,4,6-trinitro-benzenesulfonic acid (TNBS) are established agents for inducing acute and chronic colitis [ 17 20 ]. In this preliminary study, we found that administration of 3 and 2.5% DSS via drinking water can respectively induce acute and chronic colitis in mice while ensuring their survival.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs such as acetic acid, propionic acid, and butyric acid are produced by gut microbiota. Some SCFAs are sources of energy for the intestinal mucosa (Xu et al, 2021). Some of these bacteria can regulate the secretion of goblet cell mucin and mucin-related genes (Caballero-Franco et al, 2007;Dharmani et al, 2011;Sperandio et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although some proinflammatory bacteria, such as Fusobacterium and Escherichia coli , were enriched, the diversity of the gut microbiota also demonstrated a downward trend ( Pavel et al., 2021 ). Butyrate is a type of short-chain fatty acid (SCFA) that plays a protective role in the intestinal barrier and maintains the barrier integrity of epithelial cells by regulating the proliferation and development of intestinal epithelial cells; due to the imbalance of the microbiota structure, the total content of butyrate in the gut of patients with UC also decreases ( Xu et al., 2021b ). In people with T2DM, there are certain similarities in gut-microbiota changes.…”
Section: The Relationship Between Uc and T2dmmentioning
confidence: 99%
“…In people with T2DM, there are certain similarities in gut-microbiota changes. The abundance of some beneficial bacteria, such as Bifidobacterium , Bacteroides , Roseburia , Faecalibacterium , and Akkermansia , showed a downward trend ( Xu et al., 2021b ). However, numerous other opportunistic pathogens showed an upward trend ( Qin et al., 2012 ).…”
Section: The Relationship Between Uc and T2dmmentioning
confidence: 99%